Odnos između dehidrogenaze laktate i apolipoproteina A1 kod pacijenata sa teškom upalom pluća: Lactate Dehydrogenase and Apolipoprotein A1 in Severe Pneumonia - Wang, Jiang; Wang, Ronghua; Zhou, Ying; Ma, Yao; Xiong, Chunyan (Journal of Medical Biochemistry, 2023)
Background: To investigate the relationship between lactate dehydrogenase and apolipoprotein A1 levels and the condition and prognosis of patients with severe pneumonia.Methods: We retrospectively collected 204 patients with severe pneumonia who were hospitalized from January 1, 2019 to December 1, 2021 in our hospital (respiratory intensive care unit (RICU)), and divided into survival group (160 patients) and death group (44 patients) according to their hospitalization outcome. The relationship between lactate dehydrogenase and apolipoprotein A1 levels and general information, disease, and treatment needs of patients with severe pneumonia was analyzed, and lactate dehydrogenase, apolipoprotein A1, neutrophil-to-lymphocyte ratio, hematocrit, C-reactive protein, calcitoninogen, D-dimer, Acute Physiology and Chronic Health Status Rating System II, and Pneumonia Severity Index scores were compared between the survival and death groups. The value of these indicators in determining the prognosis of patients was analyzed using subject operating characteristic (ROC) curves. Logistic regression was used to analyze the risk factors for death from severe pneumonia.Results: The differences were statistically significant (P0.05). There was no statistically significant difference in LDH and ApoA1 levels between male patients and female patients (P>0.05). The differences in LDH and ApoA1 levels were statistically significant (P0.05). LDH and ApoA1 levels were higher in patients with severe pneumonia with acute exacerbation of slow-onset lung or MODS during hospitalization than in patients with severe pneumonia without acute exacerbation of slow-onset lung or MODS, with statistically significant differences (P